Board Composition and Financial Performance of Agricultural Cooperative Societies in Kericho County, Kenya - Kurgat, David; Gatauwa, James; Simiyu, Eddie (International Journal of Finance and Accounting, 2025)
composition and firm size on the financial performance of agricultural cooperative societies in Kericho County, Kenya Methodology: The study targeted 84 agricultural cooperative societies in Kericho County. Data was obtained from 49 agricultural cooperative societies’ annual reports using a data extraction form covering the period between 2017 and 2022. Findings: Panel regression analysis was used and the findings indicated that board composition had a negative and significant influence on the return on investment of the agricultural cooperative societies Unique Contribution to Theory, Practice and Policy: The study concluded that board composition has a negative and significant influence on the return on investment. The study also revealed that firm size had a significant moderating effect on the relationship between board composition and return on investment. The study recommended that the management of cooperative societies develop policies focusing on promoting diversity and expertise within board composition.